Optimalisasi Pengendalian Persediaan Bahan Baku CV. Dirga Eggtray Pinrang Menggunakan Model Probabilistik pada Kondisi Pemesanan Ulang dan Kehilangan Penjualan - Aprizal Resky; Aidawayati Rangkuti; Georgina M. Tinungki (Department of Mathematics, Hasanuddin University, 2022)
This research discusses about the comparison of raw material inventory control CV. Dirga Eggtray Pinrang. It starts with forecasting inventory for the next 12 periods using variations of the time series forecasting method, where the linear regression method provides accurate forecasting results with a Mean Absolute Percentage Error (MAPE) value of 1,9371%. The probabilistic models of inventory control used are the simple probabilistic model, Continuous Review System (CRS) model, and Periodic Review System (PRS) model. The CRS model with backorder condition is a model that provides the minimum cost of Rp. 969.273.706,20 per year compared to another probabilistic model with the largest difference of Rp. 1.291.814,95 per year, with the optimum number of order kg, reorder level kg, and safety stock kg.